ADAPTASI MODEL PEMBELAJARAN 70 20 10 PADA AGENDA 1, 2, DAN 3 PELATIHAN DASAR CALON PEGAWAI NEGERI SIPIL - Rahman, Alpha Fadila Juliana; Kamaliah, Naily (Komunitas Manajemen Kompetitif, 2023)
The Civil Servant Candidate Basic Training (Latsar CPNS) is designed to meet the needs of shaping the character of civil servants (ASN) and serves as a crucial foundation for the establishment of a service-oriented government. The participants of CPNS LIPI (integrated with BRIN) are not only located in Indonesia but are also scattered across various countries, engaged in research activities that cannot be abandoned, necessitating the implementation to be conducted through distance learning. The selection of methods and learning model approaches becomes crucial to ensure effectiveness and to ensure that participants comprehend the materials presented by facilitators. The 70-20-10 Learning Model is an approach that not only focuses on classroom learning but also emphasizes a combination of effective learning, with 70% through challenging workplace assignments, 20% task implementation and problem-solving, and 10% from training and reading. The research aims to (1) determine whether e-learning can strengthen participants' understanding during Massive Open Online Courses (MOOC), (2) explore the adaptation of the preferred learning model by participants from Science and Technology Human Resources (SDM Iptek) and Management of Science and Technology Human Resources (SDM Manajemen Iptek), and (3) observe the preference for adapting the 70-20-10 learning model in learning agendas 1, 2, and 3 through e-learning. The study's sample consists of Latsar CPNS Grade III participants from LIPI (integrated with BRIN), comprising three cohorts, with a total of 69 participants. The research instrument utilized in this study is a questionnaire distributed to training participants using a Likert scale. Data processing is carried out using descriptive statistics, as well as inferential statistics with Fisher Exact Test and Factor Analysis. The research results indicate that (1) E-learning in Latsar CPNS BRIN is capable of reinforcing the agenda 1, 2, and 3. (2) The adaptation model more favored by participants from SDM Iptek is 70-10-20. Meanwhile, the learning model more preferred by SDM Management Iptek is the 20:70:10 learning model. (3) In the deepening of agenda 1 material, participants are more suited to the formal learning model (10). For Agenda 2 material, participants tend to favor social learning (20). Meanwhile, for Agenda 3 material, participants prefer a combination of formal learning and experiential learning (10-70).